Efektifitas Pemanfaatan Rumah Tunggu Kelahiran (RTK) Bahari di Sinjai sebagai Wujud Inovasi Pelayanan Publik - Asriadi Asriadi; Sumardi Asriadi; Jusniaty Jusniaty (Journal of Government Insight, 2021)
This paper aims to analyze how effective the use of the Waiting House is Birth (RTK) in accommodating the residents of Pulau Sembilan. Using descriptive analysis qualitatively through indicators of the mechanism and effectiveness of its use along with community response on the existence of the RTK. The results show that RTK as one of the 99 The Government's Public Service Innovations have had a positive impact on services in the field of public health, Sinjai Regency in general and Pulau Sembilan in particular. The utilization of the Marine RTK in Sinjai Regency is categorized as a means of services that are very effective in accommodating the community's primary health care rights Pulau Sembilan is especially for pregnant women, and the delivery process and pre-care guarantees and post-delivery, in addition to the responsiveness of managers and medical personnel in providing service to patients and their families is an added value in proving that the concepts of assurance, responsiveness, tangiables, reliability and empathy can be realized maximally.